Air/Missile Defense, Counterproliferation And Security Policy Planning : Implications for Collaboration Between United States and the Gulf co-operation Council Countries - Edited by Davis, Jacquelyn K. Dr.; Perry, Charles M. Dr.; Al-Suwaidi Jamal S. Dr. (Abu Dhabi The Emirates Center for Strategic Studies and Research, 1999)
Providing an assessment of evolving air and missile threats confronting the countries of the Gulf Cooperation Council, this volume highlights the impact of trends involving missiles and weapons of mass destruction on the balance of power in the Arabian Gulf region.
Include Index and Illustration
Keywords: United States -- Nuclear nonproliferation -- Weapons of mass destruction